Optimal fractionation scheme for lymphocyte infiltration in glioblastoma multiforme radiotherapy - Iturri, Lorea; Gilbert, Cristéle; Espenon, Julie; Bertho, Annaïg; Potiron, Sarah; Juchaux, Marjorie; Prezado, Yolanda (Frontiers in Oncology, 2025)
PurposeRadioresistant and immunosuppressive tumors, such as glioblastoma multiforme (GBM), remain a challenge, as current clinical approaches—surgical resection and chemoradiation—do not yet provide effective treatment. Immunotherapy (IT) has emerged as a powerful tool in cancer; however, phase III clinical trials in GBM have yielded unsuccessful results, likely due to its critical dependence on preexisting antitumor immunity. Given its immunomodulatory potential, radiotherapy (RT) could serve as a tool to induce tumor inflammation and enhance responsiveness to IT. However, the optimal radiation configuration required to achieve the critical level of tumor inflammation for IT success remains elusive. This study assessed the most effective dose fractionation scheme for maximizing immune cell infiltration into tumors.Materials and methodsTwo orthotopic rat glioma models with differing vascularization and immunogenicity were irradiated with three dose fractionation schemes. Tumor immune cell populations were analyzed by flow cytometry.ResultsA single high dose (25 Gy) or extreme hypofractionation is required to elicit a significant immune infiltration in tumors.ConclusionsUsing RT as an immune primer in GBM would require very high and toxic doses with conventional RT methods. While 25 Gy is used in conventional stereotactic radiosurgery, such a high dose is typically limited to small brain volumes. Novel approaches, such as FLASH-RT or minibeam RT, offer alternatives to mitigate toxicity while achieving the required doses.